Análisis de la brecha de género en ingreso y permanencia en carreras stem en la Universidad de los Andes (2021)
This text seeks to understand the gender gap in STEM careers, seeking first to characterize the gap and subsequently analyzing the factors that determine career choice and the possibility of dropping out or regretting pursuing a career in STEM areas, using as a case of study at the University of Los Andes. It is specifically investigated for the role of the examples or role models, and the intrinsic barriers that students face due to their gender condition once they enter the University. Descriptive methods are used to characterize the gender gap over time; and econometric, which allow evaluating the difference by gender in the incidence of the factors of interest, mentioned above. The results of this study indicate that although there are no differences in the role played by the examples or role models in the lives of the students, there are significant differences regarding the gender of the example, which is directly related to what is She has studied in the literature on the representation of women in science and its broad influence on career choice. In addition, it is shown that the climate within the career, particularly in relation to classmates, can represent an additional difficulty for women who enter such programs, which can influence the possibility of dropping out or regretting it. your decision.